2020
DOI: 10.1177/0146167220936054
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Emoticon: Are There Unintentional Cues of Emotion in Email?

Abstract: Email and text-based communication have become ubiquitous. Although recent findings indicate emotional equivalence between face-to-face and email communication, there is limited evidence of nonverbal behaviors in text-based communication, especially the kinds of unintentional displays central to emotion perception in face-to-face interactions. We investigate whether unintentional emotion cues occur in text-based communication by proposing that communication mistakes (e.g., typos) influence emotion perception. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…For example, Vignovic and Thompson (2010) found that the error impression penalty was reduced when perceivers believed the actor was from a foreign culture. Blunden and Brodsky (2021) found a similar error-penalty mitigating effect of perceptions of sender emotionality, as the error was partly attributed to the overwhelming experience of emotion rather than wholly to sender incompetence. Relatedly, those whose messages included typos received a reduced professionalism penalty when it was clear that they had more difficulty physically typing the message (i.e., composing it on an iPhone rather than computer; Carr & Stefaniak, 2012).…”
Section: Moderators Of the Effects Of Virtual Impression Management B...mentioning
confidence: 79%
See 1 more Smart Citation
“…For example, Vignovic and Thompson (2010) found that the error impression penalty was reduced when perceivers believed the actor was from a foreign culture. Blunden and Brodsky (2021) found a similar error-penalty mitigating effect of perceptions of sender emotionality, as the error was partly attributed to the overwhelming experience of emotion rather than wholly to sender incompetence. Relatedly, those whose messages included typos received a reduced professionalism penalty when it was clear that they had more difficulty physically typing the message (i.e., composing it on an iPhone rather than computer; Carr & Stefaniak, 2012).…”
Section: Moderators Of the Effects Of Virtual Impression Management B...mentioning
confidence: 79%
“…Vignovic and Thompson (2010) showed that negative perceptions of error-laden email senders were attenuated when participants learned that the author was a non-native English speaker from outside the United States. In a parallel illustration, Blunden and Brodsky (2021) showed that the intelligence penalty of typos was reduced in emotional contexts, which provided an alternative explanation for the error (emotional interference). In a third study, highlighting moderators of the effect of typos on impressions, Carr and Stefaniak (2012) revealed that the negative impact of grammatical errors on perceptions of an email sender's professionalism was mitigated by the inclusion of a signature element indicating that the message was more challenging to physically compose (e.g., "sent from my iPhone").…”
Section: Nonverbal Behaviormentioning
confidence: 99%
“…An attempt to reconstruct asynchronously the presence of others through non-contextualized emotional traces left in the tool seems therefore rather hopeless. Some students overtly reported in the open-ended questions that they disposed of other tools to interact with colleagues, such as instant messaging, which provided a more holistic form of interaction, providing cognitive, social and affective support at the same time (Blunden & Brodsky, 2020;Cheshin et al, 2011;Parkinson, 2008). This directly questions the interest of disposing of a dedicated tool, even when it implements an emotion structure that would be difficult to obtain in general purpose environment as an instant messaging application.…”
Section: Perceived Usefulness Is Promising At First But Drops With Co...mentioning
confidence: 99%
“…Notably, the recognition of emotions from vocal or bodily expressions applies to various emotions and is not limited to a small selection [22]. In digital communication, observers also recognized a person's emotion from emoticons [5,23], written statements [24,25], or even typos in emails [26]. Collectively, research on facial, bodily, vocal, verbal, and symbolic expressions indicates that observers can perceive emotions of another person via diverse channels.…”
Section: Emotion and Emotion Perceptionmentioning
confidence: 99%